Termination of pre‐hospital resuscitation by anaesthesiologists – causes and consequences. A retrospective study. Issue 2 (27th November 2016) - Mikkelsen, S.; Lossius, H. M.; Binderup, L. G.; Schaffalitzky de Muckadell, C.; Toft, P.; Lassen, A. T.
Abstract : Aim: Differentiating between a newly deceased patient and the lifeless patient in whom immediate resuscitation is required may be facilitated by a pre‐hospital anaesthesiologist. The purpose of our study was to investigate to what extent and why the pre‐hospital anaesthesiologist pronounced life extinct in situations where an emergency medical technician (EMT) would have been required to resuscitate. Methods: All lifeless patients seen pre‐hospitally by the anaesthesiologist‐manned Mobile Emergency Care Unit in Odense, Denmark, from 2010 to 2014 were retrospectively studied. Results: Of 17 035 contacts, 1275 patients were lifeless without reliable signs of death. In 642 of these patients (3.8%) resuscitation was initiated (median age 68 years). The remaining 633 patients (3.7%) were declared dead at the scene without any resuscitation attempt (median age 77 years). These latter patients would have been attempted resuscitated, had the anaesthesiologist not been present. In 54.5% of cases where documentation was available in the patient records, reasons for not resuscitating these patients included time elapsed from incident to contact with physician, 'overall assessment', chronic disease, or do‐not‐resuscitate order. Conclusion: In one patient in 30, the MECU refrained from futile resuscitation in cases where legislation required an EMT to initiate resuscitation. This practice reduced unethical attempts of resuscitation, reduced unnecessary emergency ambulance transports, and reduced the work load of the hospital resuscitation teams for one unnecessary alarm every third day. Differentiating between lifeless patients and dead patients not exhibiting reliable signs of death, however, is a complex task which is only sparsely documented.